2007
DOI: 10.1002/ijc.22489
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐apoptotic role of TWIST and its association with Akt pathway in mediating taxol resistance in nasopharyngeal carcinoma cells

Abstract: TWIST, a basic helix-loop-helix transcription factor, has been reported to be associated with development and progression of human cancer. Recently, over expression of TWIST is found in cancer patients with shorter survival and poor response to chemotherapy. Previously, we found that upregulation of TWIST was responsible for the development of acquired resistance to taxol in a nasopharyngeal carcinoma (NPC) cell line, HNE1-T3 (Wang et al., Oncogene, 2004;24:274). In this study, we investigated the underlying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 31 publications
4
44
0
Order By: Relevance
“…This phenotypic behavior is associated with extensive genetic reprogramming, most notable through the actions of a family of transcription factors such as Snail, Zeb [31], FOXC2, HMGA and Twist. These factors play critical roles in mesoderm formation during embryonic development and can protect cells from apoptosis in vitro [33,34]. The sensitivity of tumor cells to the EGFR tyrosine kinase inhibitor erlotinib has been reported to correlate with EMT status in multiple cancer lines.…”
Section: Discussionmentioning
confidence: 99%
“…This phenotypic behavior is associated with extensive genetic reprogramming, most notable through the actions of a family of transcription factors such as Snail, Zeb [31], FOXC2, HMGA and Twist. These factors play critical roles in mesoderm formation during embryonic development and can protect cells from apoptosis in vitro [33,34]. The sensitivity of tumor cells to the EGFR tyrosine kinase inhibitor erlotinib has been reported to correlate with EMT status in multiple cancer lines.…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports suggest that high levels of Twist-1 confer cancer cells resistance to various chemotherapeutic drugs (Pham et al, 2007;Zhang et al, 2007;Shiota et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Twist-1 transactivates the PKBb promoter and a positive association between elevated levels of Twist-1 and PKBb has been found in late-stage breast cancer samples (Cheng et al, 2007). PKB in turn might behave as a functional mediator of Twist-1 and is involved in Twist-mediated chemotherapeutic drug resistance (Cheng et al, 2007;Zhang et al, 2007). Interestingly, Saethre-Chotzen syndrome resulting from Twist-1 haploinsufficiency displays decreased expression of Cbl ubiquitin ligase, resulting in the accumulation of phosphatidylinositol-3-kinase (PI3K) and increased PI3K/PKB signaling (Guenou et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…32 Enhanced expression of TWIST and ectopic expression of Id-1 have been separately found to protect nasopharyngeal cancer cells from taxol-induced cell death. [33][34][35] Wang et al 36 have reported that silencing of the CK8 gene increased cisplatin toxicity in HONE1 nasopharyngeal cancer cells. Mei et al 37 have observed that there was enhanced chemosensitivity to bleomycin and cisplatin, following siRNA-mediated knockdown of LMP1 in EBV-positive C666-1 cells.…”
Section: Discussionmentioning
confidence: 99%